PENINGKATAN PENGUASAAN KOSAKATA ARAB DAN KEMAMPUAN BAHASA KOMUNIKATIF MELALUI METODE COMMUNICATIVE LANGUAGE TEACHING - Shofuro, Fina Hilyatus; Umar Manshur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The limited ability of students to use Arabic vocabulary communicatively remains a persistent challenge in Arabic language education, particularly within religious-based educational institutions. This study aims to critically examine the implementation of the Communicative Language Teaching approach in enhancing students’ mastery of mufradat (vocabulary) and their communicative competence within the Islamic Studies Program at MAN 1 Probolinggo. Employing a qualitative case study design, data were collected through classroom observations, in-depth interviews and document analysis involving teachers, mentors and students. The findings indicate that the integration of Communicative Language Teaching with educational games, daily Arabic language immersion and context-based learning strategies significantly contributes to improved vocabulary acquisition, increased speaking confidence, and enhanced linguistic accuracy in authentic communicative contexts. Moreover, the boarding school environment which facilitates sustained and active language practice emerged as a critical factor in the internalization of the target language. These findings underscore the potential of the Communicative Language Teaching approach as an innovative and transformative pedagogical model that effectively integrates language acquisition, religious values and an engaging learning atmosphere. As a result, students develop into active, confident, and morally grounded communicators in Arabic.